Retardation of Mild Steel Corrosion in Analogous Schiff Bases with Different Electronic Environments - Athirah Dzolin, Syaidah; Bahron, Hadariah; Mohd, Yusirie; Zakiah Nor Hashim, Nor; Huda Abdul Halim, Nurul (International Journal of Engineering and Technology, 2018)
Two Schiff bases namely (E)-2-((phenylimino)methyl) phenol (SA1) and (E)-2-methoxy-6-((phenylimino)methyl) phenol (SA2) were produced via reaction of phenylamine with 2-hydroxybenzaldehyde and 2-hydroxy-3-methoxybenzaldenyde, respectively. The structures were elucidated through spectral and physicochemical techniques of melting point, elemental analysis (C, H and N), 1H Nuclear Magnetic Resonance (NMR) and Infrared (IR) spectroscopy. The distinctive n(C=N) and d(OH) peaks for SA1 and SA2 appeared at 1615 and 1613    cm-1 and at 13.27 and 13.37 ppm, respectively. Electrodeposit both compounds on mild steel at 0.05 M concentration in 0.3 M NaOH was established through cyclic voltammetry (CV) and chronoamperometry (CA) methods. Yellow and brownish Schiff base layers were observed to be formed on the mild steel specimens. The coated and uncoated mild steel specimens were tested for their corrosion behavior using the Tafel Extrapolation Method (TEM) in 0.5 M NaCl.  Results demonstrated that mild steel coated with SA2 through CA technique at potential +0.90 V showed the highest inhibition efficiency, hence indicating a superior surface coverage, with 97.20 % inhibition efficiency; while SA1 recorded the highest inhibition efficiency of 93.83 % at coating potential of +1.35 V.